Recent developments on Bi-based oxychalcogenide materials with thermoelectric and optoelectronic applications: an overview. (December 2022) - Parida, A.; Senapati, S.; Naik, R.
Abstract: Recently, layered oxychalcogenides have been extensively studied as promising thermoelectric materials. These materials have ionic oxide with alternative covalent chalcogenide layers, resulting in many interesting electronic properties. The materials also enable the tuning of their properties via chemical substitutions at the coexisting layers. Recently, bismuth (Bi)-based oxychalcogenides have attracted many scientists from the field of material research because of their distinctive structure, high carrier mobility, and excellent environmental stability, making them suitable candidates for high-performance electronic and optoelectronic applications. In this present report, we have presented a comprehensive review of recently developed Bi-based oxychalcogenides. The simplest Bi-oxychalcogenides are in the ternary form (Bi2 O2 Ch, Ch = S, Se, Te). We start with an introduction and classify the compounds based on sulphide, selenide, and telluride with their fundamental properties. In addition to that, different synthesis methods of oxychalcogenides along with their applications are discussed in detail. Different device applications of related materials, including photodetectors, transistors, optical switches, and artificial synapses, are also presented. Graphical abstract: Bi-based oxychalcogenides are generally thermoelectric materials along with superconducting and optical properties. The schematic diagram represents the synthesis methods and associated device applications of Bi-based oxychalcogenides. Image 1 Highlights: The Bi-based oxysulphide, oxyselenide, and oxytelluride presents a distinct structure and properties. The solid-state reaction method is useful for experimental study of samples in the conditions of doping and defectiveness. Substituting of block layer of BiS2 generate in-plane chemical pressure and enhance the superconductivity of the material. The high ZT value of oxychalcogenide is achieved by tuning the electrical conductivity via doping. The Bi-oxychalcogenides have device applications like photodetector, transistors, optical switches, and artificial synapses.